Photochromism and electrochemistry of a dithienylcyclopentene electroactive polymer - Wesenhagen, Philana (Langmuir : the ACS journal of surfaces and colloids, 2008)
A bifunctional substituted dithienylcyclopentene photochromic switch bearing electropolymerisable methoxystyryl units, which enable immobilization of the photochromic unit on conducting substrates, is reported. The spectroscopic, electrochemical, and photochemical properties of a monomer in solution are compared with those of the polymer formed through oxidative electropolymerization. The electroactive polymer films prepared on gold, platinum, glassy carbon, and indium titanium oxide (ITO) electrodes were characterized by cyclic voltammetry, X-ray photoelectron spectroscopy (XPS), and atomic force microscopy (AFM). The thickness of the films formed is found to be limited to several monolayer equivalents. The photochromic properties and stability of the polymer films have been investigated by UV/vis spectroscopy, electrochemistry, and XPS. Although the films are electrochemically and photochemically stable, their mechanical stability with respect to adhesion to the electrode was found to be sensitive to both the solvent and the electrode material employed, with more apolar solvents, glassy carbon, and ITO electrodes providing good adhesion of the polymer film. The polymer film is formed consistently as a thin film and can be switched both optically and electrochemically between the open and closed state of the photochromic dithienylethene moiety